2020
DOI: 10.1177/0734242x20910234
|View full text |Cite
|
Sign up to set email alerts
|

An eco-friendly epoxy polymer binder for the treatment of Tunisian harbor sediments: Laboratory investigations for beneficial reuse

Abstract: The management of dredged sediments poses serious environmental and economic problems because of their geochemical properties and in particular their pollutant content. In this research, marine sediments from Tunisian harbors were collected to study their beneficial reuse as construction materials using an eco-friendly polymer binder. Experimental investigations include the determination of physicochemical, mineralogical, and environmental parameters of sediments from the Sidi Mansour and Sidi Youssef areas in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Polymers are frequently utilized because they are economical 106,107 and environmentally beneficial. [108][109][110] Polymer-modified mortar (PMM) is made by combining a polymer modification with polymeric cement mortar, such as poly vinyl acetate (VAc), vinyl ester of versatic acid (VeoVa), acrylic, SB latex, and ethylene vinyl acetate (EVAc). A polymer called EVAc is frequently used to enhance the properties of concrete mortar as well as cement.…”
Section: Admixtures Based On Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers are frequently utilized because they are economical 106,107 and environmentally beneficial. [108][109][110] Polymer-modified mortar (PMM) is made by combining a polymer modification with polymeric cement mortar, such as poly vinyl acetate (VAc), vinyl ester of versatic acid (VeoVa), acrylic, SB latex, and ethylene vinyl acetate (EVAc). A polymer called EVAc is frequently used to enhance the properties of concrete mortar as well as cement.…”
Section: Admixtures Based On Polymersmentioning
confidence: 99%
“…Some polymer materials are often used to modify and improve cement‐based materials' rheological characteristics, setting time, mechanical characteristics, and toughness 4,96–105 and progressively create novel organic as well as inorganic composite cement‐based materials. Polymers are frequently utilized because they are economical 106,107 and environmentally beneficial 108–110 . Polymer‐modified mortar (PMM) is made by combining a polymer modification with polymeric cement mortar, such as poly vinyl acetate (VAc), vinyl ester of versatic acid (VeoVa), acrylic, SB latex, and ethylene vinyl acetate (EVAc).…”
Section: Admixtures Based On Polymersmentioning
confidence: 99%
“…Partial or total substitution of natural sand as aggregate in mortars, concretes or in unfired bricks is a common valorization of dredged sediments [87][88][89][90][91], with actual production of effective harbors' accropodes [84], pedestrian and vehicles pavers [92], synthetic cobblestones [93] or eco-friendly foamed concrete [94]. In some cases, a synthetic polymer replaces Portland cement to produce polymer mortars with epoxy resin [95,96], or floor-covering concrete tiles with polyester resin [97]. Silt content and soluble organic matter, two intrinsically linked parameters, may impair mechanical and durability properties of produced mortars and concretes (hydration, setting time, compressive strength, shrinkage strain).…”
Section: Integration Of Contaminated Sediments In Circular Economymentioning
confidence: 99%
“…The results highlighted that sediments can most suitably be substituted for 5% of the cement used. Lightweight aggregates manufactured from dredged sediments have been studied in many research works [ 6 , 7 , 8 , 9 , 10 ], and the results have shown their suitability for large-scale production due to their availability, homogeneity, mineralogical and chemical composition.…”
Section: Introductionmentioning
confidence: 99%